2005
DOI: 10.1038/sj.bjc.6602735
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A as a marker for prognosis and chemotherapy response in advanced breast cancer

Abstract: We wanted to study cyclin A as a marker for prognosis and chemotherapy response. A total of 283 women with metastatic breast cancer were initially enrolled in a randomised multicentre trial comparing docetaxel to sequential methotrexate-fluorouracil (MF) in advanced breast cancer after anthracycline failure. Paraffin-embedded blocks of the primary tumour were available for 96 patients (34%). The proportion of cells expressing cyclin A was determined by immunohistochemistry using a mouse monoclonal antibody to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 20 publications
4
39
0
Order By: Relevance
“…Ki67 and mitotic activity have recently been included in the St Gallen guidelines [8], but the role of other proliferation markers, such as cyclin A, is still debated. Cyclin A has been associated with a worse outcome in breast cancer patients in some studies [1,[9][10][11] but others were unable to confirm this finding [2,12,13]. Reasons for discrepant results include small numbers of patients (only two studies included more than 200 patients) and differences in lymph node status, cut-points, end-points and follow-up times, and adjuvant systemic treatment.…”
Section: Introductionmentioning
confidence: 84%
“…Ki67 and mitotic activity have recently been included in the St Gallen guidelines [8], but the role of other proliferation markers, such as cyclin A, is still debated. Cyclin A has been associated with a worse outcome in breast cancer patients in some studies [1,[9][10][11] but others were unable to confirm this finding [2,12,13]. Reasons for discrepant results include small numbers of patients (only two studies included more than 200 patients) and differences in lymph node status, cut-points, end-points and follow-up times, and adjuvant systemic treatment.…”
Section: Introductionmentioning
confidence: 84%
“…However, studies have revealed that tumour grade is also associated with survival in MBC [26,56]. A subanalysis of a phase III trial in which patients received either methotrexate plus 5-fluorouracil or docetaxel as second-line therapy demonstrated a significant association in multivariate analysis between histological grade and overall survival [57]. Ninety-six patients had evaluable immunohistochemical samples, and the HR for grade 3 vs grade 1 or 2 was 1.95 (Table 3); although the P value was not reported, the 95% CI did not cross 1, suggesting a significant difference.…”
Section: Tumour Gradementioning
confidence: 97%
“…[ 39 ] Cyclin A 2 is a prognostic indicator in early-stage cancers and has been reported overexpressed in many types of cancers including breast cancer, liver cancer, lung cancer, soft tissue sarcoma, leukemia, and lymphoma. [ 54 ] It is associated with the proliferation rate of these disorders and is a promising anti-cancer target by targeting the cyclin A 2 substrate recruitment element called the cyclin binding groove (CBG). [ 55 , 56 ] The direct detection limit of cyclin A 2 was 0.5 nM by using fl uorescent-labeled p21 (WAF-1) derived cyclin A 2 binding sequence and taking advantage of graphene as highly effi cient fl uorescence quencher.…”
Section: Optical Methodsmentioning
confidence: 99%